How useful do communities find the health and wellness centres? A qualitative assessment of India’s new policy for primary health care - Shriyuta Abhishek; Samir Garg; Vikash Ranjan Keshri (BMC Primary Care volume 25, Article number: 91 (2024), 2024)
Starting in 2018, Indian government has established more than 100,000 Health and Wellness Centres (HWCs) to increase rural population’s access to primary health care. It is crucial to know how useful people find the services of HWCs.
Keywords: Health infrastructure; Health workforce